The effect of general anesthesia and conscious sedation in endovascular thrombectomy for acute ischemic stroke: an updated meta-analysis of randomized controlled trials and trial sequential analysis - Peng, Zhi; Luo, Wenmiao; Yan, Zhengcun; Zhang, Hengzhu (Frontiers in Neurology, 2023)
Objectives General anesthesia (GA) and conscious sedation (CS) are common methods for endovascular thrombectomy (EVT) in acute ischemic stroke (AIS). However, the risks and benefits of each strategy are unclear. This study aimed to summarize the latest RCTs and compare the postoperative effects of the two methods on EVT patients. Materials and methods We systematically searched the database for GA and CS in AIS patients during EVT. The retrieval time was from the creation of the database until March 2023. The quality of the studies was evaluated using the Cochrane risk of bias tool. Random-effects or fixed-effects meta-analyses were used to assess all outcomes. Results We preliminarily identified 304 studies, of which 8 were included. Based on the pooled estimates, there were no significant differences between the GA group and the CS group in terms of good functional outcomes (mRS0-2) and mortality rate at 3 months (RR = 1.09, 95% CI: 0.95–1.24, p = 0.23) (RR = 0.95, 95% CI: 0.75–1.22, p = 0.70) as well as in NHISS at 24 h after treatment (SMD = −0.01, 95% CI: −0.13 to 0.11, p = 0.89). However, the GA group had better outcomes in terms of achieving successful recanalization of the blood vessel (RR = 1.13, 95% CI: 1.07–1.19, p < 0.0001). The RR value for the risk of hypotension was 1.87 (95% CI: 1.42–2.47, p < 0.00001); for pneumonia, RR was 1.43 (95% CI: 1.07–1.90, p = 0.01); and for symptomatic intracerebral hemorrhage, RR was 0.94 (95% CI: 0.74–1.26, p = 0.68). The pooled RR value for complications after intervention was 1.03 (95% CI, 0.87–1.22, p = 0.76). Conclusion In patients undergoing EVT for AIS, GA, and CS are associated with similar rates of functional independence. Further trials of a larger scale are needed to confirm these findings.